Avaliação funcional pré e pós programa de exercício físico de pacientes em hemodialise - Lima, Fabiano Francisco; Miranda, Regina Célia Vasques de [UNESP]; Silva, Renata C. Rossi [UNESP]; Monteiro, Henrique Luiz [UNESP]; Yen, Lin Sheng [UNESP]; Padulla, Susimary Aparecida Trevisan [UNESP]; Fahur, Barbara dos Santos (My University, 2013)
Model Study: An experimental study Introduction: Chronic Kidney Disease (CKD) refers to a syndromic diagnosis which leads to a progressive and irreversible loss of renal function. A hemodialysis patient may have limitations in functional capacity, pulmonary function and respiratory musclular strength impacting in quality of life. Objective: To evaluate the effects of an exercise program on pulmonary function, functional capacity, quality of life and pain in patients undergoing hemodialysis. Methodology: The study included 28 patients of both genders, women and men aged between 40 and 60 years undergoing dialysis at the Kidney Institute, Santa Casa de Misericordia in Presidente Prudente-SP. Primary outcomes included respiratory muscular strength measurements assessed by manovacuometry. The functional capacity was evaluated by a six minute walking test. A life quality questionnaire was applied to evaluate quality of life (SF36-KDQOL). Lung function was evaluated by spirometry. Pain was assessed by a visual analogue scale. The exercise program consisted of training 3 times a week for 40 minutes on hemodialysis during eight weeks. At the end of the program all patients were reassessed. Results: There was no significant difference in the values of FVC and FEV1 before and after the exercise program as well as the index Tiffenau. The value of post MIP was significantly higher than the value obtained in the pre program. For variable MEP no significant difference was found. Functional capacity evaluations showed that there were no significant differences (p> 0.05). The evaluation of quality of life, about the domains of specific areas of CKD showed statistical significance when comparing the list of symptoms and problems with overloading of renal disease and professional role. Indicators related to pain were significantly reduced after the program (P <0.05). Discussion: A chronic kidney patient faces complex situations of physical, social and financial aspects. Although no statistically significant results were found in all variables, the study corroborates to others found in the literature, which suggests that an exercise program can be positive for this population. Conclusion: Although lung capacity and functional capacity did not submit changes to the end of the study, reduced levels of pain, fatigue and dyspnea suggest improvement in functional performance after exercise programs.

Modelo do estudo: Estudo experimental. Introdução: A Doença Renal Crônica (DRC) refere-se a um diagnóstico sindrômico de perda progressiva e irreversível da função renal. O paciente submetido à hemodiálise pode apresentar limitações na capacidade funcional, função pulmonar e força muscular respiratória, com consequentes prejuízos na qualidade de vida. Objetivo: Avaliar os efeitos de um programa de exercício físico sobre a função pulmonar, capacidade funcional, qualidade de vida e dor, em pacientes que realizam hemodiálise. Metodologia: Participaram do estudo 28 pacientes de ambos os sexos, com idade entre 40 e 60 anos, em programa de hemodiálise no Instituto do Rim da Santa Casa de Misericórdia de Presidente Prudente-SP. A força muscular respiratória foi avaliada pela manovacuometria, a capacidade funcional, pelo TC6', a qualidade de vida, pelo questionário KDQOLSF, a função pulmonar, pela espirometria e a dor, pela EVA. Após as avaliações, os pacientes iniciaram o programa de exercícios, que foi desenvolvido três vezes por semana, durante 40 minutos em hemodi- álise, por oito semanas. Ao final do programa, os pacientes foram reavaliados. Resultados: Não houve diferença significativa dos valores da CVF e VEF1 pré e pós-programa de exercícios, assim como do Índice de Tiffenau. O valor da PImax pós-programa foi significativamente maior que o obtido na avalia- ção pré-programa. Para a variável PEmax, não foi encontrada diferença significativa. As avaliações da capacidade funcional inicial e final não apresentaram diferenças significativas (p>0,05). A avaliação da qualidade de vida, quanto aos domínios das áreas específicas da DRC, mostrou que houve significância estatística, ao comparar a lista de sintomas e problemas com a sobrecarga da DRC e papel profissional. Os indicadores relativos à dor foram reduzidos, após o programa (p<0,05). Discussão: O DRC enfrenta situações complexas de dependência física, social e financeira. Apesar de não apresentar resultados estatisticamente significativos em todas as variáveis avaliadas, este estudo, corroborando outros encontrados na literatura, sugere um programa de exercício físico, com aspectos positivos para essa população. Conclusão: Embora a capacidade pulmonar e a capacidade funcional (TC6') não tenham apresentado alterações ao final do experimento, os níveis reduzidos de dor, cansaço e dispneia sugerem melhora do desempenho funcional, após programas de exercício físico para DRC.
Functional evaluation pre and post physical exercise program for patients in hemodialysis
Keywords: Hemodialysis; Physical Activity; Spirometry; Quality of Life; Hemodiálise; Atividade Física; Espirometria; Qualidade de Vida